Immature reticulocyte fraction in guiding stem cell harvest in autologous peripheral blood stem cell transplant - Md Noor, Sabariah; Leong, Chooi Fun; Cheong, Soon Keng (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
Peripheral blood (PB) CD34+ cells enumeration is currently the most reliable method to guide the timing of stem cell harvest. However, its usage is restricted by being technically challenging, costly, and time-consuming. Immature reticulocyte fraction (IRF) determination, which is simpler and cheaper and has a faster turn-around time, has been proposed for a similar purpose. The purpose of this study is to evaluate the value of IRF in guiding stem cell harvest and examine the correlation between IRF and PB CD34+ cells count. Daily pre-harvest tests, i.e. PB CD34+ cells and IRF from 21patients scheduled for autologous PBSC transplant were assessed. Stem cells harvests were commenced when the PB CD34+ cell count were more than 10 cell/ul. A total of 205 pre-harvest tests were analysed. Following stem cell mobilisations, both the IRF and PB CD 34+ cell counts rose with a variable pattern. In this study, we observed that the IRF peaks preceded the PB CD34+ count by 2 days. On the day of stem cell harvest, all the peak IRF values were >0.3. The PB CD34+ cell counts correlated with the harvested stem cell yield, whereby r2 = 0.77, p < 0.021. In autologous stem cell mobilisation, we believe that IRF is a useful screening tool to predict the rise of the PB CD34+ cell counts as it is a simple, fast and less costly. An IRF of > 0.3 may be used as a cut-off value for the initiation of PB CD34+ quantification prior to stem cell harvest.